Impact of nutritional status on the emergence of coronary obstructive diseases: Integrative review - Santos , Carla Karoline Jesus; Cobra, Ana Cássia Lira de Amorim (Seven Editora, 2023)
Introduction: The change in the nutritional profile of the Brazilian population brought about by changes in the structure of the diet of individuals, which correlates with economic, social, demographic and health-related changes, has led to the worsening of nutritional problems, since the state of malnutrition to obesity, which corroborates the increase in non-transmissible chronic diseases. Objective: To describe the effect of nutritional status on the occurrence of coronary artery disease. Methodology: integrative review, carried out through a bibliographic survey, in July and August 2022, in the Virtual Health Library (VHL), Scientific Electronic Library Online (SciELO), ScienceDirect, Scopus (Elsevier), U.S. National Library of Medicine National Institute of Health (PubMED) and Web of Science, with the Health Science Descriptors (DeCS) and their correspondents in Spanish and Portuguese: “Coronary Stenosis”, “Coronary Disease”, “Coronary Artery Disease”, “Coronary Occlusion” and “Nutritional Status”, for crossing the DeCS, the Boolean operators “OR” and “AND” were used. With regard to ethical aspects, all authors of the articles were respected. Results: 433 potentially eligible publications were identified, of which 13 were selected. These came from nine different nationalities. Of which 23.07% were published in the year 2021. Regarding the level of evidence of the studies, most (53.84%) were level III. Conclusion: In relation to this work, it was shown that the low intake of proteins, fibers, vitamins, minerals and high intake of carbohydrates and fats were associated with the increase and severity of CAD. Thus, the most prudent and scientifically viable thing is for the general population to consume a balanced diet rich in antioxidants from fresh fruits, vegetables and whole grains.DOI:https://doi.org/10.56238/emerrelcovid19-018